Analysis of Magnetic Component Manufacturing Cost Through the Application of Time-Driven Activity-Based Costing - Nik Nurharyantie, Nik Mohd Kamil; Mohd Yazid, Abu; Nurul Farahin, Zamrud; Filzah Lina, Mohd Safeiee (Springer, 2020)
With a continuous innovation of Electrical & Electronic (E&E) industry, the magnetic component gets increasing demand from customer and their target in production is 5000 units in one shift. Hence, to fix a product cost and to achieve the target finished product are the case study on E&E industry. In other words, the company’s product cost is calculated using traditional cost accounting based on volume product of magnetic component. This cost is unable to record accurately the changes of resources used to manufacture the product. The aim of this work to analyze the manufacturing cost of magnetic component incurred on production of E&E industry and time for good by Time-Driven Activity-Based Costing system (TDABC). In methodology, TDABC will be developed by using seven stages which are identify resources group and service processes of all activity and sub-activity, estimate cost of all resources supplied, estimate practical capacity, calculate capacity cost rates, develop time equation, determine time estimates for each sub-activity, and estimate capacity cost required. By having the analysis, loss manufacturing cost winding toroid core can be identified at −MYR2967504.12 and identifying of unused capacity (−889200.12 min) is capable to improve the time efficiency.